Consistent strut-and-tie modelling of deep and short beams and hollow-core slabs at ambient and elevated temperatures - Fan, Shengxin (Nanyang Technological University, 2021)
The primary aim of this research is to examine the feasibility of applying strut-and-tie model (STM) to RC deep and short beams at ambient temperature and under fire conditions, deep beams under unequal and/or unsymmetrical loading arrangement, and PCHC slabs with non-uniform cross sections and no web reinforcement. In this regard, the main objectives of this thesis are to (1) examine experimentally structural fire behaviour of axially-restrained and unrestrained short beams, with shear-span-to-effective-depth (a/d) ratio ranging from 1.50 to 2.50, followed by the development of a general STM-based approach for simulating the response of short beams subjected to fire; (2) conduct analytical and experimental studies on RC deep beams under combined effects of load inequality, load asymmetry, and elevated temperatures; (3) develop and validate a refined STM approach for both symmetrically- and unsymmetrically-loaded deep beams at ambient temperature; and (4) establish and verify a STM approach to predict the web-shear capacity of PCHC slabs at ambient temperature. To achieve the research objectives, two series of tests are conducted on seven short beams and six deep beams under elevated temperatures. The first series is to investigate experimentally the effects of a/d ratio and thermal-induced axial restraint on structural fire behaviour of short beams, while Series II was for unsymmetrically-loaded RC deep beams at elevated temperatures. The experimental data are utilised to establish proposed STM approaches for assessing the shear resistances and fire durations of deep and short beams when exposed to fires. Based on the experimental and analytical studies, it was found that: (i) The presence of elevated temperatures alters failure model of deep and short beams to a less brittle failure mode with an increase in mid-span deflection; (ii) The studied parameters, namely, a/d ratios, thermal-induced axial restraint, load inequality and load asymmetry, greatly affect the respective structural responses of the short or deep beams; and (iii) The proposed STM approaches provide consistently conservative predictions in failure time and capacity of deep and short beams at elevated temperatures. Furthermore, a refined STM solution is proposed to establish an optimal STM geometry for RC deep beams under unsymmetrical loadings by adopting the theory of elasticity and the criterion of minimum strain energy. The proposed STM is validated against 140 test results, including 14 unsymmetrically-loaded deep beams and 126 symmetric deep and short beams, and finite element models (FEMs) for the 14 unsymmetrically or unequally loaded deep beams. The STM predictions yield good agreement with experimental results and FEM predictions. Additionally, to evaluate the web-shear capacity of PCHC slabs at ambient temperature, the study proposes a combined single- and two-panel STM for PCHC slabs with a/d ≤ 3.00 and a multi-panel STM for PCHC slabs with a/d > 3.00. Model predictions are validated against 46 experimental data of PCHC slabs collected from literature. The model is capable of giving consistent predictions with different slab thicknesses and a/d ratios.